Applying the Keystone Design Perforator Island Flap Concept in a Variety of Anatomic Locations: A Review of 60 Consecutive Cases by a Single Surgeon. Issue 1 (July 2017) - Lanni, Michael Alan; Van Kouwenberg, Emily; Yan, Alan; Rezak, Kristen M.; Patel, Ashit
Abstract : Background: The keystone design perforator island flap has been gaining popularity for reconstruction of cutaneous defects. Published experience of this technique in North America is limited predominantly to the trunk and extremities; our study aims to demonstrate expanding applications. Methods: Retrospective chart review was conducted on all patients who underwent keystone flap reconstruction by a single surgeon. Outcomes of interest were wound healing complications (WHC) and surgical site infections (SSI). Mean follow up time was 24.4 months. Results: Sixty consecutive flaps were performed with an overall WHC rate of 26.7% and SSI rate of 11.7%. Reconstructed sites included 25 lower extremity, 20 trunk, 5 upper extremity, and 10 head and neck. Flap size averaged 405.6 cm 2 (range 16-2303). Wound healing complications were associated with coronary artery disease ( P = 0.04) and traumatic defects ( P = 0.043). Surgical site infections were associated with coronary artery disease ( P = 0.02) and flap size of 251 to 500 cm 2 ( P = 0.039), although this association was not seen among flaps greater than 500 cm 2 . Although more common in lower extremity reconstructions, no statistically significant associations between flap location and WHC ( P = 0.055) or SSI ( P = 0.29) were identified. There were no reconstructive failures and no patients required reoperation. Conclusions: This series demonstrates the versatility of the keystone flap in a wide variety of anatomic locations, with similar complication rates to those previously reported and no reoperations. Flap design was frequently modified based on the anatomical topography and adjacent subunits. To our knowledge, this is the largest and most diverse North American series of keystone flap reconstructions to date.